Risk of Cesarean Delivery among Nulliparous Asian-Indian Women with Term Singleton Pregnancies - Prabhu, Malavika; Melamed, Alexander; Bryant, Allison S. (American Journal of Perinatology, 2019)
Objective Asian-Indian women are a growing population in the United States, but little data exist about their risk of cesarean delivery (CD). We characterize the odds of CD among Asian-Indian women and determine whether neonatal birth weight modifies this relationship.Study Design This is a retrospective cohort study using an administrative perinatal database from California. We identified 1,029,940 nulliparous women with live, singleton, nonanomalous deliveries between 37 and 42 completed weeks of gestation. We performed multivariable logistic regression analyses to determine if Asian-Indian women were more likely to deliver by CD, compared with white non-Hispanic women, adjusting for sociodemographic and clinical variables. We explored if birth weight was an effect modifier, testing the interaction term's significance using Wald's test, and performed multivariable logistic regressions stratified by birth weight category.Results Asian-Indian women comprised 2.0% of the cohort. Compared with white non-Hispanic women, Asian-Indian women had an adjusted odds of 1.41 (95% confidence interval: 1.36–1.46) for CD. However, we noted effect modification of birth weight on the odds of CD by race/ethnicity (p < 0.001). Among all birth weight categories exceeding 3,000 g, Asian-Indian women had higher odds of CD than white non-Hispanic women.Conclusion Asian-Indian women are at greater risk of CD than white non-Hispanic women when birthweight exceeds 3,000 g.
Keywords: cesarean delivery; race; ethnicity; Asian-Indian; pregnancy; birth weight; disparities